Antecedents of Cyber Love Addiction and moderating effect of gender among Malaysian students in a university in Malaysia - Kamaliyeh, Nayerh Ghasemi (2018)
Cyber Love Addiction (CLA) associated with online addiction through social network sites is a cause of many problems both socially and individually. Today, people prefer to communicate through social network sites rather than engaging in actual conversations and face-to-face contacts with their family and friends. According to previous studies, students who are addicted to social media face many problems such as educational failure, poor academic achievement, unstable marriage, familial dissatisfaction, and irregular relationships. Furthermore, many types of cyber-crimes such as drug dealing, pornography, abusee and cheating in both genders among students and the general public had been reported. Cyber love addiction can be considered as an addiction to forming romantic relationships with strangers via social networks. The aim of this study is to determine the effect of gender as a moderator in the relationship between social capital, perceived economic well-being, and loneliness with Cyber Love Addiction (CLA) among Malaysian students by gender. The independent variables in this research include social capital, the perceived economic well-being of the family and loneliness, whilst the dependent variable is cyber love addiction with gender as the moderator. A sample of 280 Malaysian students in Universiti Putra Malaysia (UPM) were identified using a multi-stage random sampling approach. Data was collected through a survey technique. In this study, the levels of cyber love addiction, social capital, loneliness, and perceived economic well-being of the family were measured by using a selfadministered questionnaire. The data was analyzed using SPSS Ver 22 for descriptive statistics whilst the research hypothesis was studied using statistical methods such as Pearson’s correlation, independent sample t-test, Chi-square test, and multiple linear regression (MLR). Moderating analysis was done using PROCESS macro.The results of the descriptive analysis of demographic characteristics among the respondents showed that the majority of the respondents were female (63.2%), Muslim (71.8%) and single (91.4%). Considering the program, the results showed that the majority of the students (89.6%) were pursuing bachelor degrees. The result revealed that the overall CLA and four sub-components (tolerance, withdrawal, conflict, and relationship experience) were significantly different between the two genders where the male students had a higher mean score of CLA as compared to the female students. Perceived economic well-being had a significant and negative effect on the total CLA; social capital had a positive and significant effect on the total CLA whilst the effect of loneliness was not statistically significant. Some of the background variables such as “daily hours spent on Facebook”, “spend time alone on Internet web surfing”, and “spend time alone on Internet chatting” were significantly influenced on total CLA. The results of the moderating effect of gender indicated that the relationship between PEW and social capital with CLA was significantly moderated by gender while the relationship between loneliness with CLA was not significantly moderated by gender. As a conclusion, CLA may be understood as a behavioral addiction which may be affected by many factors such as social and psychological issues. The implication of this study may be used by policy and decision makers which could be of help for them on related issues for future programs. In summary, implications of the theory, Gender and Development, may be beneficiary to Malaysian academics and contribute towards policy making.